2008
DOI: 10.1111/j.1600-0447.2008.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for the metabolic syndrome in community psychiatric patients prescribed antipsychotics: a quality improvement programme

Abstract: The programme's success may be partly attributed to the use of a widely-accepted audit standard, and bespoke change interventions that directly addressed barriers to screening identified by the participating clinical teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 40 publications
2
69
2
1
Order By: Relevance
“…Les alertes émises par les agences sanitaires n'ont pas fait la preuve de leur efficacité [8,9]. Toutefois, des études ont montré l'efficience de programmes visant à améliorer la surveillance métabolique [24,25]. Il est donc essentiel d'insister lors de la formation initiale et continue des médecins sur les risques métaboliques associés à la prescription d'ASG, et sur la nécessité de surveiller les paramètres métaboliques cliniques (notamment le poids) et biologiques lors de l'initiation d'un traitement antipsychotique.…”
Section: Discussionunclassified
“…Les alertes émises par les agences sanitaires n'ont pas fait la preuve de leur efficacité [8,9]. Toutefois, des études ont montré l'efficience de programmes visant à améliorer la surveillance métabolique [24,25]. Il est donc essentiel d'insister lors de la formation initiale et continue des médecins sur les risques métaboliques associés à la prescription d'ASG, et sur la nécessité de surveiller les paramètres métaboliques cliniques (notamment le poids) et biologiques lors de l'initiation d'un traitement antipsychotique.…”
Section: Discussionunclassified
“…The Prescribing Observatory for Mental Health recently introduced two national programmes to improve medicines' management practices in mental health organisations across the UK. 20,22 The first, designed to reduce rates of prescribing of high-dose and combinations of antipsychotics failed to bring about a change in practice, despite identifying factors associated with dubious prescribing practices and targeting a number of change interventions. In the second programme, rates of physical health monitoring doubled after the introduction of a 12-month intervention programme.…”
Section: Discussionmentioning
confidence: 99%
“…The level of monitoring in many cases is far from being satisfactory, especially in the community. A large audit of 48 assertive outreach teams in the UK, including 1966 patients, revealed that more than 60% of this population had no evidence of screening for BP, obesity, blood glucose and lipid profile [Barnes et al 2008]. However, those numbers significantly improved 1 year after implementing a blend of approaches to influence the behaviour of mental health professionals.…”
Section: Discussionmentioning
confidence: 99%